APPLICATION CARDIAC TROPONIN IN CARDIOVASCULAR DISEASES OTHER THAN ACUTE CORONARY SYNDROME: A SYSTEMATIC REVIEW - Paranoan, Anissa; Paranoan, Asriany (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Increased cardiac troponin concentrations in acute coronary syndrome (ACS) identify patients with ongoing cardiomyocyte necrosis who are at increased risk. However, with the use of more precise assays, cardiac troponin increases are commonly noted in other cardiovascular conditions as well. The aim: This study aims to show application cardiac troponin in cardiovascular disease other than acute coronary syndrome. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 211 articles, whereas the results of our search on SagePub brought up 221 articles. The results of the search conducted for the last year of 2013 yielded a total 65 articles for PubMed and 95 articles for SagePub. The result from title screening, a total 19 articles for PubMed and 30 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Increased cardiac troponin indicates increased risk for adverse outcome in patients with various cardiovascular conditions beyond ACS. Routine measurement of cardiac troponin concentrations can however, not be generally recommended unless there is a suspicion of ACS.